Keanekaragaman Herba di Kawasan Mangrove Muara Aluh-Aluh - Hidayah, Ismatul; Hardiansyah, Hardiansyah; Noorhidayati, Noorhidayati (Universitas Al Azhar Indonesia, 2022)
Herbs are plants with moist stems that grow wild along roadsides or on the unmaintained ground. Herbs are more commonly associated with plants that are harmful to civilization, even though they have numerous uses in life, including traditional medicine, ornamental plants, and contextual instructional resources. People are unaware of herbs and plants categorized as herbs, which is one of the reasons why they are considered hazardous plants. A mangrove forest is a type of forest with a tidal environment; plants that may grow in mangrove forests are characteristic vegetation, notably salt-tolerant plants. The goal of this research was to describe the plant variety in the Muara Aluh-Aluh Mangrove Area. The data was gathered in the 500-meter-long Muara Aluh-Aluh Mangrove Area, which was divided into ten locations separated by 50 meters. A plot of 1 m x 1 m with as many as 4 pieces was made at each place using the line transect method and oriented diagonally. The quantity and varieties of herbaceous plants found in the plot were counted as samples. According to the findings of the study on herbaceous plant diversity in the Muara Aluh-Aluh Mangrove area, there are 21 different varieties of herbaceous plants with a diversity index of 2.66, putting them in the medium diversity category.Keywords - Diversity, Herbs, Mangroves, Muara Aluh-Aluh